الجمعيات الخيرية ودورها الدعوي والتربوي -جمعية الإرشاد والإصلاح -مكتب ورماس -أنموذجا -دراسة تطبقية - زيدان, كلثوم; لشهب, أحلام (University of Eloued-جامعة الوادي, 2022)
"تناولت الدراسة موضوع ""الجمعيات الخيرية ودورها الدّعويّ والتّربويّ.. مكتب جمعية الارشاد والاصلاح بورماس ولاية الوادي ، -دراسة تطبيقية"".. وقد اشتملت الدّراسةُ على مقدّمة وثلاثة فصول، يمثّل الفصل الأول الإطار المنهجيّ للدراسة حيث اشتمل على إشكالية الدراسة وتساؤلاتها الفرعية، وأهميتها، وأسباب اختيار الموضوع، ثم أهداف الدراسة، والدراسات السابقة، والمصطلحات والمنهج المتّبع. أمّا الفصل الثّاني: الإطار النّظريّ للدراسة، فجاء بعنوان الدّعوة والتّربية والجمعيات الخيرية، واشتمل على ثلاثة مباحث: المبحث الأول ماهية الدّعوة، والمبحث الثّاني ماهية التربية، والمبحث الثّالث ماهية الجمعيات الخيّرية. وفي الفصل الثاّلث المتمثل في الإطار التّطبيقيّ للدّراسة، والذّي حمل عنوان جمعية الارشاد والاصلاح، كان الحديث في مبحثين: المبحث الأول بعنوان جمعية الارشاد والإصلاح ، والمبحث الثاني بعنوان جمعية الإرشاد والاصلاح مكتب ورماس. وقد استخدمنا في دراستنا المنهج الوصفيّ مع استخدام أداة المقابلة للحصول على المعلومات والبيانات التي تفيد وتخدم دراستنا، وقد أظهرت الدّراسة عدّة نتائج أهمها: أنّ جمعية الإرشاد الاصلاح بمكتب ورماس تؤدّي دورها في الدّعوة والتّربية، وذلك من خلال أهدافها ومشاريعها وإنجازاتها التّي حقّقتها في الدّعوة والتّربيّة. ""The study dealt with the topic ""Charitable associations and their advocacy and educational role office of the Association for Guidance and Reform of Ourmas""، a model that is one of the charitable associations in the State of El-oued. The aim is to answer the questions raised in order to achieve the objectives and results achieved in the role of charities in advocacy and education، in particular the Association for Guidance and Reform in the Ourmas Office. This study included an introduction and three chapters، chapter I being the methodological framework for a study where it included the study's problem، the importance of the study، the reasons for the study، the study's objectives، the study's questions، the study terminology and the methodological procedures for the study. Chapter II: Theoretical framework for a study entitled ""Advocacy، Education and Charitable Associations""، which includes three investigators: First Research: What is Advocacy، Second Research: What is Education and Third Research: What is Charitable Associations. Chapter III is the applied framework of the study، entitled ""The Association for Guidance and Reform"". It includes two researchers: the first research entitled ""The Association for National Guidance and Reform"" and the second research entitled ""The Association for Guidance and Reform"" of the Ourmas Office. In our study، we used the descriptive curriculum، using the interview tool to obtain information and data that would benefit and serve our study. The study showed several results، the most important of which: The Guidance and Reform Society of the Ourmas Office plays its role in advocacy and education through its objectives، projects and achievements in advocacy and education. "
مذكرة ماستر
Keywords: الجمعيات الخيرية-الدعوة-التربية; Charitable societies - advocacy - education